Environment and the OECD guidelines for multinational enterprises corporate tools and approaches. (Organisation for Economic Co-operation and Development, 2005)
This book provides a detailed examination of the environment chapter of the OECD Guidelines for Multinational Enterprises, other relevant provisions of the Guidelines and gives concrete ideas and guidance to enterprises wishing to implement the Guidelines.--Publisher's description.